Successful treatment of multidrug resistant Klebsiella pneumoniae using dual carbapenem regimen in immunocompromised patient. (2017) - El Nekidy, Wasim S.; Mooty, Mohamad Y.; Attallah, Nizar; Cardona, Lyssette; Bonilla, Maria Fernanda; Ghazi, Islam M.
Abstract: This report describes a longitudinal case of immunocompromised patient post kidney transplant who was admitted to our institution repeatedly for treatment of various infections caused by multi-drug resistant Klebsiella pneumoniae. The patient was successfully treated with a combination of ertapenem/meropenem on multiple occasions despite the elevated MICs. Our observations corroborate previous preclinical studies and case reports showing the efficacy of double carbapenem regimens against resistant Enterobacteriaceae.